Extension activities with caregivers of people with Alzheimer's disease: Challenges in times of COVID-19 (Research, Society and Development, 2021)
This study aimed to report the experience of organizing the extension activities of the AMICA group (Integrated Multiprofessional Assistance to Caregivers of People with Alzheimer's Disease), in a remote environment during the period of social isolation due to the COVID-19 pandemic. This is an experience report on the extension activities that took place in the first half of 2020. Several remote virtual interaction actions were carried out, such as sending videos, music, information pamphlets, and telephone calls. In addition, actions were carried out, such as mailing letters and home visits. Even though through remote actions, it was possible to give a voice to the caregiver, listen to their stories, encourage physical activities, work with health education and encourage their socialization. It was noticed the importance of actions to reduce the distance between the group members, reduce anxiety and understand the importance of self-care. Additionally, the activities represented a relevant health education strategy during the COVID-19 pandemic.